Coconut Husks and Eggshells Liquid Organic Fertilizer's Effect on The Growth and Calcium Levels of Kale - Susetyawati, Nabila Junisky; Asngad, Aminah (Universitas Muhammadiyah Surakarta, 2023)
Kale (Brassica oleracea var. achepala) is an essential vegetable for human development due to its calcium levels. Lack of hares in the soil is the cause of the decline in kale production. The purpose of this study was to test eggshell and coconut husk liquid organic fertilizers for kale plant growth and calcium levels. The research was conducted at the green house of Biology Education, FKIP UMS. Liquid organic fertilizer dosage (P1 = 100 ml and P2 = 150 ml ) and time intervals (W1 = 3 days once and W2 = 5 days once) were tracked using the completely randomized design (RAL) with control treatment as comparison and 3 times replication. Data was analyzed using two-way ANOVA. The plant height, number of leaves, fresh weight, and calcium levels are the variables that were observed. The study revealed that P2W2 treatment had the highest development rate, with average number of leaves of 14 strands, growth height of 13.3 cm, fresh weight of 51.5 g, and calcium levels of 0.141%. Based on the results of the research, it was shown that coconut husks and eggshell liquid organic fertilizer are effective on the growth and increase calcium levels of kale.